Analysis of 1st grade and 5th grade textbooks and primary school students' views about personal traits in gender role in society - Atay, Mesude; Danju, Ipek (Elsevier Science Bv, 2012)
This study investigates whether the textbooks used in Turkish Republic of Northern Cyprus (TRNC) schools carry stereotyped images and whether students view stereotypical representations of gender on personal traits are different with the respect of their gender and grade level. For the aim of this study, the primary 1st and 5th and 17 grade school textbooks were read in detail to find out gender stereotypic representations that matched with the categorie of personal traits. The questionnaire were developed to see the primary 1st and 5th grade students view about gender role releted to personal trait. Female and male are generally represented in a stereotyped way in the school textbooks; The numbers of personal traits representations were evaluated, being brave, being dependent, independent, clever, leader, creative, supportive, rich, hardworking, and lazy are for male personal traits. Beautiful, sweet, emotional, happy, sad, surprised and friendly are given for female personal traits according to the school textbooks content. Active, passive, aggressive, and sensitive are equal for these two gender representations. Students views with the respect of their gender show the similar results with the textbooks. Female students see most of the personal traits for both gender however male studnts' views reflect the stereotype personal traits in gender roles in society.
Cyprus International Conference on Educational Research (CY-ICER) -- FEB 08-11, 2012 -- Middle E Tech Univ No Cyprus Campus, CYPRUS
Keywords: Gender role; Gender stereotype; Textbooks; Primary school; Personal traits